2010
DOI: 10.1007/s10585-010-9337-9
|View full text |Cite
|
Sign up to set email alerts
|

ERK activation of p21 activated kinase-1 (Pak1) is critical for medulloblastoma cell migration

Abstract: We previously identified that overexpression of the platelet-derived growth factor receptor (PDGFR) is associated with metastatic medulloblastoma (MB) and showed that PDGF treatment increases ERK activity and promotes MB cell migration. In this study, we investigated whether ERK regulates Rac1/ Pak1 signaling and is critically linked to MB cell migration. Herein we demonstrate that PDGF-BB treatment of MB cells induces concomitant activation of PDGFRβ, MEK1/ERK, Rac1 and Pak1, but suppresses Rho activity, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…Note that experiments utilized serum in order to better match the conventional Boyden chamber assays used by previous work from our lab 1,21 and others 3 that utilize the assays as benchmarks for migration. As demonstrated previously in the literature, 41 Boyden chamber experiments using serum-starved MB cells vs. non-serum starved cells confirmed near identical chemotactic behaviors (data in Supplemental Fig. 1).…”
Section: Methodssupporting
confidence: 87%
“…Note that experiments utilized serum in order to better match the conventional Boyden chamber assays used by previous work from our lab 1,21 and others 3 that utilize the assays as benchmarks for migration. As demonstrated previously in the literature, 41 Boyden chamber experiments using serum-starved MB cells vs. non-serum starved cells confirmed near identical chemotactic behaviors (data in Supplemental Fig. 1).…”
Section: Methodssupporting
confidence: 87%
“…Altered expression and/or activation of PAK1 is evident in various cancers, including brain, pancreas, colon, bladder, ovarian, hepatocellular, urinary tract, renal cell carcinoma, thyroid, and breast cancers ([137146], reviewed in [147]). Of these cancers, the role for PAK1 in breast cancer has been studied to the most extent ([58, 80, 87, 148152], reviewed in [147, 153]).…”
Section: 2 P21-activated Kinase 1 (Pak1)mentioning
confidence: 99%
“…These studies have shown that MB migration is dependent on estrogen-receptor (Belcher et al, 2009), c-Met (Guessous et al, 2010, and PDGFR-activation (Yuan et al, 2010). Via a combination of wound-healing assays and modified Boyden chamber assays, two groups showed that PDGF-induced overexpression of Rac1, a Rho GTPase, is involved in MB cell migration and invasion, whereas knockdown of Rac1 expression dramatically inhibited migration and invasion of MBs (Chen et al, 2011;Yuan et al, 2010). These findings may promote the evaluation of Rac1 as a novel therapeutic agent impairing medulloblastoma PDGF-induced migration/invasion.…”
Section: Transwell Migration Assaysmentioning
confidence: 99%